COVID-19 and the Creative Music Ecology - Ng, Karen; Thomson, Scott (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Karen Ng and Scott Thomson reflect on the impact of the pandemic on the field of creative improvised music from their perspectives as performers, composers, and presenters. Along the way, they explore the nature and limitations of livestream performance, and articulate why, as co-programmers of the Guelph Jazz Festival, they have not presented livestream or other digital programming during the pandemic.